Erneut über eine Familie von Fabiern aus Apulum - Ardevan, Radu (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This is a broad treatment of the family of T. Fabius Ibliomarus, a Treverian merchant who became decurio kanabarum at Apulum under Commodus (CIL III 1214). His sons, Aquileiensis and Pulcher, rose to the equestrian order. The first one fulfilled the militiae equestres (AE 1971, 385 and 1992, 1487), the second one seems to have exercised a procuratorian charge (CIL III 1157). There are moreover other Fabii at Apulum, who could belong to the same family. In particular Fabia Lucilla, a daughter and wife of equestrian rank, honored as mater collegiorum fabrum et centonariorum in Colonia Aurelia Apulensis (CIL III 1297), is surely a descendant of Ibliomarus. This case-study demonstrates the social advancement of immigrants in the local gentry, and some kinships between the elite from the canabae of the Legio XIII Gemina and the aristocrats of the neighboring town Apulum.